2018
DOI: 10.7554/elife.36246
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition gates supralinear Ca2+ signaling in Purkinje cell dendrites during practiced movements

Abstract: Motor learning involves neural circuit modifications in the cerebellar cortex, likely through re-weighting of parallel fiber inputs onto Purkinje cells (PCs). Climbing fibers instruct these synaptic modifications when they excite PCs in conjunction with parallel fiber activity, a pairing that enhances climbing fiber-evoked Ca2+ signaling in PC dendrites. In vivo, climbing fibers spike continuously, including during movements when parallel fibers are simultaneously conveying sensorimotor information to PCs. Whe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
37
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(42 citation statements)
references
References 74 publications
3
37
1
Order By: Relevance
“…In addition, adaptive changes in the vestibulo-ocular reflex elicited by CF optogenetic activation switched from increase to decrease depending on whether MLIs were co-activated using optogenetics 18 . Finally, MLIs gate supralinear CF-evoked Ca2+ signaling in the PC dendrite 41 . These studies suggest that the valence of learning is graded by MLI activity.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, adaptive changes in the vestibulo-ocular reflex elicited by CF optogenetic activation switched from increase to decrease depending on whether MLIs were co-activated using optogenetics 18 . Finally, MLIs gate supralinear CF-evoked Ca2+ signaling in the PC dendrite 41 . These studies suggest that the valence of learning is graded by MLI activity.…”
Section: Discussionmentioning
confidence: 99%
“…First, MLIs appeared to be relatively inactive during quiescence suggesting that inhibition of CF-evoked dendritic Ca 2+ signaling in PCs (Callaway et al, 1995;Rowan et al, 2018) does not account for the reduced size of spontaneous events. In fact, in Crus II, chemogenetic disinhibition of the molecular layer has no effect on spontaneous Ca 2+ event amplitudes (Gaffield et al, 2018). Interestingly, we observed that MLIs in Crus I were coactivated with PCs in response to sensory cue presentation.…”
Section: Dendritic-wide Ca 2+ Signaling In Pc Dendrites Is Exclusivelmentioning
confidence: 56%
“…For analysis of Ca 2+ event size, we focused on discrete, isolated responses (Gaffield et al, 2018). Thus, we avoided potential uncertainties associated with GCaMP6f non-linearity (Chen et al, 2013) for overlapping events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Episodes of hyp state can be due, in principle, to synaptic inhibition coactively occurring during activity patterns associated with cerebellar learning (Suvrathan and Raymond, 2018). Indeed, it was recently demonstrated that optogenetic activation of interneurons in the molecular layer strongly affects PF synaptic plasticity and motor learning, as well as CF-mediated signalling Gaffield et al, 2018). Another possibility is that hyp state episodes are intrinsically generated in PNs by a "priming" signal that hyperpolarises the cell, for instance by activating a K + conductance.…”
Section: Role Of the Initial V M And Implication For Synaptic Plasticitymentioning
confidence: 99%